BIM Enabled Sustainable Facility Management - Rahman, Md Motiar (International Journal of Integrated Engineering, 2021)
The scope of facility management spans from traditional activities like repair & maintenance, health & safety, through to real estate management, financial management, change management, and even contract management, tender and procurement, construction, and demolition and disposal of the constructed facility. It therefore requires considering sustainability aspects of construction, which are better addressed through sustainable design strategies. A consolidated but holistic framework has been conceptualized to ensure sustainability in facility management, especially to practice in building and AEC (architecture, engineering and construction) sectors. Although testing and validation is needed, the conceptualized framework is expected to achieve sustainability in the relevant sectors.